Santri Gobal Gabul and the Praxis of Tawhid: Rethinking Inclusive Tolerance Education through Al-Faruqi’s - Habibi, Rohim; Nurdi, Nurdi; Huda, Miftahul; Kholis, Nur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
While inclusive tolerance education is frequently examined within formal academic institutions, research on non-formal religious communities as transformative agents remains scarce. Furthermore, Al-Faruqi’s epistemology is often discussed as an abstract philosophical framework with limited empirical application in grassroots social contexts. This study addresses this gap by theorizing a model of inclusive tolerance education through an exploration of the praxis of tawhid within the Santri Gobal Gabul community. Employing a field-based qualitative approach with a descriptive phenomenological design, data were gathered through participant observation, documentation, and in-depth interviews with pesantren caretakers, religious counselors, santri, and interfaith community members. The findings reveal that the Santri Gobal Gabul community implements a grounded Islamic education model through the Ngopi (Ngolah Pikir) tradition, an epistemological process that bridges sacred texts with social reality. This practice manifests Al-Faruqi’s principles of Unity of Truth, Unity of Mankind, and Unity of Life, where tolerance is internalized through direct action (learning by doing), involving the transformation of the heart (fathul qulub) and openness of mind (fathul ‘aql). This study extends Al-Faruqi’s epistemology into lived community contexts, proposing a practice-based model of inclusive Islamic education that dismantles social hierarchies and fosters transformative social cohesion. This theoretical contribution offers a significant reference for developing contextual and responsive multicultural education to mitigate contemporary social polarization.